Microenterprise Peso Acceptance in El Paso, Texas - J. Pisani, Michael (Universidad Autónoma de Nuevo León, 2013)
Utilizing a unique sample of 253 microenterprise border retailers from El Paso, Texas, this paper explores the possibility of cash payment from cross-border shoppers using Mexican pesos. We find that one-fifth of microenterprise retailers in El Paso accept payment in Mexican pesos. Increased peso acceptance rates are associated with retailer proximity to Mexico and business segment in which the retailers compete. El Paso microenterprises are also more likely than their medium- to large-business counterparts to allow payments to be made using Mexican pesos. The opportunity cost of currency substitution is examined for accepting and yet-to-accept firms. JEL Classification: M21, F31, D22.